2004
DOI: 10.1017/s1357729800054485
|View full text |Cite
|
Sign up to set email alerts
|

Effects on inbreeding of different strategies aimed at eliminating scrapie sensitivity alleles in rare sheep breeds in The Netherlands

Abstract: The Dutch scrapie eradication programme aims at the exclusive use of homozygous ARR/ARR breeding rams by the end of 2004. As a consequence, breeds with a small population size and a low frequency of the ARR allele may suffer unacceptable losses of genetic diversity and high inbreeding levels. We simulated three breeding strategies to assess their efficacy in eliminating scrapie sensitive alleles and their effect on inbreeding levels. Under mild selection, both homozygous and heterozygous ARR rams were used ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…This problem was studied by Windig et al (2004) who have concluded that severe selection for ARR leads to unacceptably high rates of inbreeding, especially in rare breeds with low ARR frequencies. Nevertheless, if the selection program is designed for a longer period of time, the negative impact of inbreeding and possible founder effects can be minimized, as discussed by Gama et al (1992) in the framework of introgression of a desirable transgene from one founder into a breeding population, which is similar to selection for fixation of a desirable genetic marker from one or a few founders, as was the case here for some of the breeds.…”
Section: Discussionmentioning
confidence: 99%
“…This problem was studied by Windig et al (2004) who have concluded that severe selection for ARR leads to unacceptably high rates of inbreeding, especially in rare breeds with low ARR frequencies. Nevertheless, if the selection program is designed for a longer period of time, the negative impact of inbreeding and possible founder effects can be minimized, as discussed by Gama et al (1992) in the framework of introgression of a desirable transgene from one founder into a breeding population, which is similar to selection for fixation of a desirable genetic marker from one or a few founders, as was the case here for some of the breeds.…”
Section: Discussionmentioning
confidence: 99%
“…It is very likely that this is a result of the synergism between two factors: the unplanned breeding of animals Virus Genes (2011) 43:153-159 157 with ARR allele in the parent flocks and the small populations of the breeds. That is why, in these breeds and Replyan sheep it is appropriate to apply the Dutch model of selection, which includes mild (using homozygous and heterozygous ARR rams for breeding, without preferences), moderate (using preferentially homozygous ARR rams) and severe selection (using only homozygous ARR rams) [48]. The prevalence of the ARR allele in Local Stara Zagora sheep (41.25%) allows the simultaneous elimination of homozygous VRQ.…”
Section: Discussionmentioning
confidence: 99%
“…The third risk identified was that of breeds being taken through a genetic bottleneck due to the eradication programme (Windig et al, 2004), resulting in loss of genetic variation. The breeds most at risk are those already classified rare and those breeds with a low proportion of the ARR haplotype, which will potentially be made rare by the programme.…”
Section: Discussionmentioning
confidence: 99%
“…The approach to achieving this aim varies between countries. For example the Dutch scrapie eradication plan only allows matings using homozygous ARR rams (Windig et al, 2004), whereas the UK National Scrapie Plans allow additional options for matings using heterozygous rams carrying ARR, ARH, AHQ or ARQ (Defra, 2004). Ultimately both approaches will eradicate the VRQ haplotype and increase the frequency of the ARR haplotype, although the Dutch approach is more likely to drive the ARR to fixation in a shorter time period, with one consequence of this being a greater threat to their genetic base.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation